Fur Represses Vibrio cholerae Biofilm Formation via Direct Regulation of vieSAB, cdgD, vpsU, and vpsA-K Transcription - Gao, He; Ma, Lizhi; Qin, Qin; Qiu, Yue; Zhang, Jingyun; Li, Jie; Lou, Jing; Diao, Baowei; Zhao, Hongqun; Shi, Qiannan; Zhang, Yiquan; Kan, Biao (Frontiers in Microbiology, 2020)
Attached Vibrio cholerae biofilms are essential for environmental persistence and infectivity. The vps loci (vpsU, vpsA-K, and vpsL-Q) are required for mature biofilm formation and are responsible for the synthesis of exopolysaccharide. Transcription of vps genes is activated by the signaling molecule bis-(3′–5′)-cyclic di-GMP (c-di-GMP), whose metabolism is controlled by the proteins containing the GGDEF and/or EAL domains. The ferric uptake regulator (Fur) plays key roles in the transcription of many genes involved in iron metabolism and non-iron functions. However, roles for Fur in Vibrio biofilm production have not been documented. In this study, phenotypic assays demonstrated that Fur, independent of iron, decreases in vivo c-di-GMP levels and inhibits in vitro biofilm formation by Vibrio cholerae. The Fur box-like sequences were detected within the promoter-proximal DNA regions of vpsU, vpsA-K, vieSAB, and cdgD, suggesting that transcription of these genes may be under the direct control of Fur. Indeed, the results of luminescence, quantitative PCR (qPCR), electrophoretic mobility shift assay (EMSA), and DNase I footprinting assays demonstrated Fur to bind to the promoter-proximal DNA regions of vpsU, vpsA-K, and cdgD to repress their transcription. In contrast, Fur activates the transcription of vieSAB in a direct manner. The cdgD and vieSAB encode proteins with GGDEF and EAL domains, respectively. Thus, data presented here highlight a new physiological role for Fur wherein it acts as a repressor of V. cholerae biofilm formation mediated by decreasing the production of exopolysaccharide and the intracellular levels of c-di-GMP.